Coronavirus disease-2019: A tocsin to our aging, unfit, corpulent, and immunodeficient society - David C. Nieman (Elsevier, 2020)
Acute and chronic respiratory illnesses cause widespread morbidity and mortality, and this class of illness now includes the novel coronavirus severe acute respiratory syndrome that is causing coronavirus disease-2019 (COVID-19). The world is experiencing a major demographic shift toward an older, obese, and physically inactive populace. Risk factor assessments based on pandemic data indicate that those at higher risk for severe illness from COVID-19 include older males, and people of all ages with obesity and related comorbidities such as hypertension and type 2 diabetes. Aging in and of itself leads to negative changes in innate and adaptive immunity, a process termed immunosenescence. Obesity causes systemic inflammation and adversely impacts immune function and host defense in a way that patterns immunosenescence. Two primary prevention strategies to reduce the risk for COVID-19 at both the community and individual levels include mitigation activities and the adoption of lifestyle practices consistent with good immune health. Animal and human studies support the idea that, in contrast to high exercise workloads, regular moderate-intensity physical activity improves immunosurveillance against pathogens and reduces morbidity and mortality from viral infection and respiratory illnesses including the common cold, pneumonia, and influenza. The odds are high that infectious disease pandemics spawned by novel pathogens will continue to inflict morbidity and mortality as the world's population becomes older and more obese. COVID-19 is indeed a wake-up call, a tocsin, to the world that primary prevention countermeasures focused on health behaviors and hygiene demand our full attention and support.